From the Surau to the Madrasah: The Contribution of Sheikh Abdul Karim Amrullah's Thought to the Transformation of Malay Education - Sya'adah, Fatihatus; Abdurrahmansyah, Abdurrahmansyah; Fauzi, Muhammad (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study explores the intellectual contribution of Syekh Abdul Karim Amrullah to the transformation of Islamic education in the Malay world, particularly the shift from the traditional surau system to the modern madrasah. Using a qualitative-historical approach, the research investigates the social, intellectual, and religious contexts that shaped his educational reform movement in early 20th-century Minangkabau. Findings indicate that Amrullah played a crucial role in integrating Islamic values with modern rationality through systemic, methodological, and curricular reforms. He rejected the dichotomy between religious and secular sciences, introduced a structured class-based learning system, and emphasized moral and character education as the foundation of Islamic pedagogy. Thus, it can be concluded that Sheikh Abdul Karim Amrullah played a significant role in transforming Malay Islamic education from the traditional surau system to the modern madrasah. The principles introduced by Sheikh Abdul Karim Amrullah included curriculum reform, classical methods, and the integration of religious and general knowledge to form the basis for a rational and contextual Islamic education. His conception of madrasah represented not merely an institutional reform but a manifestation of a progressive and contextual Islamic renewal aimed at liberating the Muslim community from ignorance and colonial domination. Amrullah’s educational thought laid a vital foundation for the development of modern Islamic education in Indonesia and the broader Malay world.